2001
DOI: 10.1614/0890-037x(2001)015[0355:eosmoe]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Moisture on Efficacy of Imazethapyr in Greenhouse1

Abstract: A greenhouse study was conducted to evaluate the efficacy of imazethapyr at 35 and 53 g ai/ha applied preplant incorporated (PPI) or postemergence (POST) under various soil moisture regimes (13, 19, 25, and 50%) on barnyardgrass and red rice. Response of barnyardgrass and red rice to imazethapyr PPI was affected by soil moisture. With imazethapyr PPI, control of barnyardgrass was reduced at 50% soil moisture compared with other soil moisture regimes, and height of barnyardgrass increased as soil moisture incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 13 publications
2
17
0
3
Order By: Relevance
“…Under dry conditions, the efficacy of PRE herbicides usually decreases (Zhang et al 2001;Zanatta et al 2008); however, intensive precipitation after application of these herbicides can cause crop injury (Stickler et al 1969;Soukup et al 2004). This effect is especially important for sunflower because the selectivity of most herbicides is dependent on the position of the herbicide layer on the soil surface and the distribution of seeds on the soil profile.…”
mentioning
confidence: 99%
“…Under dry conditions, the efficacy of PRE herbicides usually decreases (Zhang et al 2001;Zanatta et al 2008); however, intensive precipitation after application of these herbicides can cause crop injury (Stickler et al 1969;Soukup et al 2004). This effect is especially important for sunflower because the selectivity of most herbicides is dependent on the position of the herbicide layer on the soil surface and the distribution of seeds on the soil profile.…”
mentioning
confidence: 99%
“…Na literatura existem relatos que a condição hídrica do solo pode ou não influenciar o controle de plantas daninhas, como exposto por Zhang et al (2001) que o herbicida imazethapyr aplicado em pós-emergência de Oryza sativa não foi influenciado pela condição hídrica, entretanto Roman et al (2005) demonstraram que Euphorbia heterophylla submetidas a aplicação de carfentrazone-ethyl apresentaram melhores controles quando estavam sem déficit hídrico. Esse fato, provavelmente, se deve ao mecanismo de ação de cada herbicida citado.…”
Section: Resultsunclassified
“…Herbicide concentration in soil inversely related to the sum of soil moisture content and soil water partition coefficient (Green & Obien 1969). Zhang et al (2001) have demonstrated that higher soil moisture at 50% can reduce the efficacy of imazethapyr when applied as preplant treatment. In this study, the treatments were applied during rainy season.…”
Section: Phyllanthus Amarus Total -----------------------------------mentioning
confidence: 99%